Virtual reconstruction of the roman villa in La Quintilla (Lorca) based on the existing physical evidence and related scientific comparisons as a reference - Sebastián F. Ramallos Asensio; Alicia Fernández Díaz; Mariano Flores Gutiérrez; Álvaro Romero Soria; Juan Martínez García (Virtual Archaeology Review)
The virtual reconstruction of archaeological sites using computer graphics is a very important tool for the verification or refutation of hypotheses in scientific research. It also is an excellent way to spread awareness Heritage with realistic images of scientific rigor.